The problems of stopping studies at the university - Regina Atstupėnienė; Irena Tiknevičienė (Lietuvos Matematikos Rinkinys)
The paper deals with the problems of higher mathematics studies of the first course of the Mechanical Faculty students, analyses the results of the test in mathematics and presents thė ways to improve the studies.